Analysis of growth, yield and control of Cophes notaticeps and Polyphagotarsonemus latus in Jatropha curcas plants under different doses of silicon - Matos, Fabio Santos; Caramori, Samantha S.; Zago, Leciana M.; Parreira, Gabriel Santin; Amaro, Camila Lariane; e Silva, Felipe de Oliveira; Rossato, Liana Verônica; Amorim, Victor Alves (Acta Iguazu, 2021)
The present study aims to evaluate the effects of Si on growth, yield and resistance of Jatropha curcas plants to Cophes notaticeps and Polyphagotarsonemus latus. The study was carried out in two consecutive years with J. curcas plants with 3 years old in 3x2 m spacing. The assays were set up with randomized complete block design with five concentrations (0, 10, 20, 40 and 80 mM L-1) and five replications. It was set up another experiment in a greenhouse following completely randomized factorial design 5x2 with five silicon concentrations (0, 10, 20, 40 and 80 mM L-1) and two water supply: daily irrigation with water volumes according to 50% and 100% of evapotranspiration, six replications and one plant per plot. The present study allows clarifying that J. curcas plants are non-accumulating plants, for accumulating less than 1% of silicon in the leaves. The low accumulation of silicon in the leaves did not significantly inferred in growth of J. curcas, however, the reduction of specific leaf area possibly occurred by the formation of a thin silica layer and reduced the yield by the decrease sunlight absorption. The silicon did not mitigated the damages by Cophes notaticeps and Polyphagotarsonemus latus by the low ability of the plant to accumulate silicon, however, is possible to affirm that the injuries severity by Cophes notaticeps is proportional to stem diameter.